Ceny niewolników w „Historia Lausiaca” autorstwa Palladiusza z Helenopolis - Milewski, Ireneusz (Studia Europaea Gnesnensia, 2018)
The paper draws on the accounts by Palladius, bishop of Bithynian Helenopolis, to gather insights into slave prices. The figures contained in the source vary to a great extent (from 3 to 20 solidii for a slave). The author verifies the information against other late antique and early Byzantine accounts regarding slave prices.